2019
DOI: 10.1080/09544828.2019.1699036
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review of product platform design under uncertainty

Abstract: With intense global competition, many enterprises adopt platform strategies to develop diverse products with a lower corresponding increase in cost and a shorter lead time. In the past, enormous efforts have been made in investigating product platforms. Recent researches and practices show that developing Uncertainty-Oriented Product Platform (UOPP) is a promising approach to improving the adaptability of enterprises to meet uncertain markets, customer requirements, technologies, policies, and regulations, etc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 93 publications
0
29
0
Order By: Relevance
“…A platform-based development can help to achieve efficient reuse across variants while facing challenges such as an increase in the frequency of introduction of new products, change of existing parts, changes in government regulations and changes in processes [15]. Han et al [16] propose the concept of Uncertainty-Oriented Product Platform (UOPP) to increase the adaptability of enterprises to uncertainties. UOPP includes platform models such as flexible product platform, adaptable product platform, market-driven product platform and sustainable product platform [16].…”
Section: Frame Of Referencementioning
confidence: 99%
See 2 more Smart Citations
“…A platform-based development can help to achieve efficient reuse across variants while facing challenges such as an increase in the frequency of introduction of new products, change of existing parts, changes in government regulations and changes in processes [15]. Han et al [16] propose the concept of Uncertainty-Oriented Product Platform (UOPP) to increase the adaptability of enterprises to uncertainties. UOPP includes platform models such as flexible product platform, adaptable product platform, market-driven product platform and sustainable product platform [16].…”
Section: Frame Of Referencementioning
confidence: 99%
“…Han et al [16] propose the concept of Uncertainty-Oriented Product Platform (UOPP) to increase the adaptability of enterprises to uncertainties. UOPP includes platform models such as flexible product platform, adaptable product platform, market-driven product platform and sustainable product platform [16]. A flexible platform considers into account uncertainties and consists of flexible elements.…”
Section: Frame Of Referencementioning
confidence: 99%
See 1 more Smart Citation
“…Han et al, 2021); fuzzy front-ends for product development (Park et al, 2021); surrogate models and computational complexity (Alizadeh et al, 2020); smart design (Pessôa & Becker, 2020); design and poverty (Jagtap, 2019); mass customization (Ferguson et al, 2014); product stigma (Schröppel et al, 2021); uncertainty (X. Han et al, 2020); decision making methods (Renzi et al, 2017); modular product design (Bonvoisin et al, 2016); or productservice systems (Vasantha et al, 2012).…”
Section: Relation To Other Surveysmentioning
confidence: 99%
“…These enterprises need to build a strong product system to resist the impact of other systems [ 14 ]. To supply niche markets, product seriation constitutes the product system, whose goal is to develop a modular platform and derive innovative products through a module configuration [ 15 ]. Numerous industrial examples have demonstrated the superiority of product seriation to ensure corporate competitiveness, such as Sony [ 16 , 17 ] and Hewlett Packard [ 18 ].…”
Section: Introductionmentioning
confidence: 99%